Penggunaan Media Sosial Sesuai Nilai Luhur Budaya di Kalangan Siswa SMA - Roswita Oktavianti; Riris Loisa (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2017)
The youth as a generation of social media users holds great control over the dissemination of information in groups and families. Social media like Facebook, Twitter, Instagram, Path, becomes a medium of expression and self-existence, and the spread of news and information. In this case, social media becomes a means of spreading the noble values of the culture that is acculturated in one's self and their surrounding environment. However, the younger generation is less aware of the role of social media as a means of spreading the noble values of culture. Information and news in social media are accepted immediately without verifying the truth. Social media is more dominantly used as a means of self-expression, without a positive contribution to other social media users, or, in this case, followers. Therefore, the younger generation needs to be briefed on the use of social media as well as the importance of using social media as a medium that communicates the noble values of culture. The briefing was conducted at SMA Santo Kristoforus 1, West Jakarta. By using survey method to know the effectiveness of the briefing, the younger generation' understanding of the use of social media before and after the briefing. The outcome of this activity, all students are able to show which information that should or should not be disseminated, able to recognize or identify false news (hoaxes), false news information, and the steps taken when receiving the false news.